Coronado National Memorial : A History of Montezuma Canyon and the Southern Huachucas - Sánchez, Joseph P. (Book collections on Project MUSE., 2017)
"Coronado National Memorial : A History of the Huachuca Mountains and Montezuma Canyon is about a place that is tied to the history, heritage, and patrimony of Spain, Mexico, and the United States as well as to regional Native American tribes. As such, thematic supplements include Spanish colonial contact, settlement, missions, Mexican Territorial Period land grants, and a history of Coronado National Memorial. Additionally, the history of Montezuma Canyon is part of the historical process that shaped the region and two countries"--Provided by publisher.